Vacuum enrichment of mango slices with isomaltulose - Do Carmo, Juliana Rodrigues; Corrêa, Jefferson Luiz Gomes; Resende, Mariana; Cirillo, Marcelo Ângelo; Telis-Romero, Javier [UNESP]; Pena, Rosinelson da Silva (FapUNIFESP (SciELO), 2024)
Vacuum is efficient for incorporating solutes of interest into fruits. In this study, the low glycemic and insulinemic index carbohydrate, isomaltulose, was incorporated into mangos slices by immersion with a vacuum pulse (VP). The influences of the combination of pulsed vacuum time at the beginning of the process (5, 10, 15, and 20 min) and vacuum pressure (24 kPa and 48 kPa, absolute pressure) in the incorporation were evaluated with the multidimensional scaling (MDS) statistical technique. Water loss (WL), solid gain (SG), water activity (aw), and color were also studied. The MDS effectively indicated that the vacuum incorporation (VI) with 10 min of VP at 48 kPa provided a product with higher SG (more enriched), WL, lightness, and lower aw and total color difference. Thus, the VI with intermediate conditions resulted in a high incorporated mango with good quality.
Enriquecimento de fatias de manga com isomaltulose
Keywords: palatinose; PVOD; Tommy atkins